Analysis and Design of Pay Structures and Scales for Medium Enterprises in The Culinary Sector in The Bali Province - Tanaya, Sintya Ismana Gardenia; Kartika, Lindawati (Jurnal Ilmiah Sumber Daya Manusia, 2024)
In Minister of Labour Regulation No. 1 of 2017, employers are obliged to establish wage structure and scale and will receive sanctions if violate. However, there are still SMEs that have not implemented it. The objectives of this study are: 1) Identify financial compensation received by restaurant employees in Bali, 2) Analyze and evaluate job positions based on internal and external comparisons, 3) Develop wage structure and scale for restaurants in Bali based on two-point method. Data collection and processing was conducted from December 2022 to August 2023, located at 10 restaurants in Gianyar, Denpasar and Badung. Type of data includes primary data (interviews and questionnaires) and secondary data from Bali Government's website and relevant literature. The methods used include descriptive analysis, salary survey, salary mapping, and two-point method. The research found that WM restaurant provides the highest compensation (83% of total role) and 100% fulfilled the Provincial and Regional Minimum Wage. As a result, WM restaurant can serve as a benchmark for compensation implementation.